The Concept of “Ren (Benevolence)” in the Eyes of Catholic Missionaries During the Ming-Qing Transition Period - FENG, Xiaoqiang (Journal of Research for Christianity in China (JRCC), 2025)
The concept of Ren仁 experienced the process of acceptance, use and interpretation in the literature left by Catholic missionaries during the Ming and Qing Dynasties. Ren was initially recognized as an ethical norm of a foreign land and could not appear in the discussion of Catholic doctrine. With the deepening of cognition, Ren began to appear in the translation of the doctrine by the missionaries. In the basic connotation of love, it gradually expanded from the reference to the restraint of sin to the overall description of God’s love. In this process, a system of benevolent ontology with God as the core was developed. Along with this is the missionary’s interpretation and transformation of the Confucian doctrine on the basis of the Catholic standard. The result is a set of conceptual systems that combine Catholicism and Confucianism. The thorough understanding of this set of conceptual systems relies on the separation of traditional external and heterogeneous perspectives as an alternative development to Confucian benevolence.